2011
DOI: 10.1007/978-1-61779-310-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated Neuropeptides for Site-Specific Microinjection

Abstract: This paper describes an experimental approach based on nanotechnology for assessing the chronic actions of short-lived neuropeptides at specific sites of the brain. This methodology combines the advantages of two different techniques: the microinjection of a suspension of peptide-containing liposomes into a specific site of the brain, and the use of liposomes as a local and sustained release nanosystem of the peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Accordingly, in vivo release study, with this same preparation (Vaz et al, 2015) indicated a sustained release of GABA from liposomes, with only ~60% of GABA release after 5 days of incubation at 37°C. Other important characteristics of these liposomes are their mean diameter of 200 nm and the incorporation of a pegylated lipid, to slow down their capture by cells for endocytosis/phagocytosis and the cell-mediated release of encapsulated drug (Frezard et al, 2011). However, the early response after exposure of NG108-15 to GL suggests that liposome capture by these cells takes place and exerts a significant effect on the proteins measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in vivo release study, with this same preparation (Vaz et al, 2015) indicated a sustained release of GABA from liposomes, with only ~60% of GABA release after 5 days of incubation at 37°C. Other important characteristics of these liposomes are their mean diameter of 200 nm and the incorporation of a pegylated lipid, to slow down their capture by cells for endocytosis/phagocytosis and the cell-mediated release of encapsulated drug (Frezard et al, 2011). However, the early response after exposure of NG108-15 to GL suggests that liposome capture by these cells takes place and exerts a significant effect on the proteins measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes are microscopic spherical vesicles, consisting of one or more concentric lipid bilayers, which isolate one or more internal aqueous compartments from external medium (Figure 1) [3,22]. They may encapsulate hydrophilic and/or lipophilic substances in the inner aqueous compartment and in the membrane respectively.…”
Section: Properties Of Liposomes: General Aspectsmentioning
confidence: 99%
“…Importantly, the membrane fluidity and surface of liposomes can be manipulated to control the drug release from liposomes. For instance, more rigid membranes usually result in lower rates of drug release [3]. When the cell-mediated drug release mechanism predominates, PEGylated liposomes also promote slower drug release.…”
Section: Properties Of Liposomes: General Aspectsmentioning
confidence: 99%
See 2 more Smart Citations